Assessment of the relevance of GaPc substituted with azido-polyethylene glycol chains for photodynamic therapy. Design, synthetic strategy, fluorescence, singlet oxygen generation, and pH-dependent spectroscopic behaviour. (16th August 2017) - Koç, Veysel; Topal, Sevinc Zehra; Aydın Tekdaş, Duygu; Ateş, Özge Dilara; Önal, Emel; Dumoulin, Fabienne; Gürek, Ayşe Gül; Ahsen, Vefa
Abstract : New synthetic route and PDT potential of symmetrically and asymmetrically substituted Ga(iii )Pcs with terminal azides. Abstract : A new efficient synthetic route was used to obtain symmetrically and asymmetrically substituted gallium(iii ) phthalocyanines (5-GaCl and6-GaCl ) containing azido groups with chlorine atoms at axial positions, using correspondingZnPc derivatives (5-Zn and6-Zn ) as precursors. The photophysical and photochemical properties—fluorescence, singlet oxygen generation, and photodegradation—of5-GaCl and6-GaCl were compared with that of5-Zn and6-Zn . Their pH-sensitive spectral changes were also investigated in detail, as tumours are more acidic than healthy tissues. Their amphiphilicity, quantified by their partition coefficient, appeared suitable for biological applications.5-GaCl and6-GaCl exhibited higher photodynamic potential than unsubstituted gallium(iii ) phthalocyanine, suggesting potential to be used as a photodynamic therapy agent.